Capital and Economic Development: A Critical Appraisal of the Recommendations of the Mackenzie Valley Pipeline Commission - Asch, Michael I. (Culture, 1982)
This paper is intended to examine the impact that Mr. Justice Berger’s recommendation on sources of capital would have on the opportunity for the Dene economy to develop along lines which remained consistent with their traditional institutions and values. It argues that Mr. Justice Berger’s view that funds should come from Government grants will ultimately have a strong negative impact in this area. An alternative, rejected by Mr. Justice Berger, that funds be obtained through rents and royalties is examined and found to be a better solution, although again fraught with difficulties. In the review a comparison between a staples theory approach as adopted by Mr. Justice Berger and a mode of production approach is made with respect to a theoretical orientation toward understanding the problems inherent in the Dene economy and its potential for development.